Integrated graphene systems by laser irradiation for advanced devices. (February 2017) - Zhao, Yang; Han, Qing; Cheng, Zhihua; Jiang, Lan; Qu, Liangti
Graphical abstract: Highlights: We summarized the significant advance on laser-directed integrated graphene devices. The state-of-the-art applications in electronic/optoelectronic devices were reviewed. The perspectives and challenges in future graphene integrated devices were discussed. Abstract: With the development of portable electronics, integrated graphene microstructures and devices have attracted increasing attention due to their environment-benign, lightweight feature with small occupied area. Laser irradiation technique with advantages of rapid processing speed, large scan area and nanometer spatial resolution has been widely studied and applied in the fabrication of various nano/microstructures of graphene materials for integrated electronic applications. This review summarizes the significant advance on laser-directed design and fabrication of integrated graphene devices, along with state-of-the-art applications in microcircuits, supercapacitors, sensors, actuators, memory chips and optoelectronic devices. The perspectives and challenges in designing and improving future graphene integrated devices are also discussed.